Analisis Kestabilan dan Rekomendasi Perbaikan Desain Lereng pada Tambang Terbuka - Muhammad Thoyib Alhadi Prabowo; Ratna Dewi; Yulia Hastuti (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2026)
This study evaluates the stability of an open-pit mine slope and proposes an optimized slope geometry based on limit equilibrium analysis. Geotechnical parameters were derived from field investigations using the Rock Mass Rating (RMR) and Geological Strength Index (GSI) classification systems, then incorporated into Slide 6.0 for slope stability analysis. The Janbu and Morgenstern–Price limit equilibrium methods were employed to determine the factor of safety (FoS). Initial simulations indicated that the analyzed slope was stable; however, the observed field failure prompted a back analysis, which identified a weak layer with reduced shear strength as the primary cause of instability. The back analysis produced FoS values of 0.774 and 1.154 using the Janbu and Morgenstern–Price methods, respectively. Based on these findings, the slope geometry was redesigned with a slope angle of 45°, a bench width of 13 m, and a bench height of 8 m. The redesigned slope increased the FoS to 1.314 (Janbu) and 1.590 (Morgenstern–Price), satisfying the recommended stability criterion. A comparison of the two methods further showed that the Janbu method consistently yielded FoS values approximately 15% lower than those obtained using the Morgenstern–Price method, indicating its more conservative predictions. The proposed design provides an effective approach for improving slope stability while highlighting the importance of incorporating back analysis to capture actual field conditions that are not represented in initial geotechnical models.